Análise econômica e gestão de custos da recria e engorda de raças zebuínas - LAUANY LIARA TAVARES MASCARENHAS (2025)
The year 2022 was marked by the recovery of the global agricultural sector, driven by the re-establishment of exports to China, after temporary embargoes in 2021, and the 22.6% growth in Brazilian exports. However, challenges such as inflation, rising production costs and the impacts of the COVID-19 pandemic and the Russia-Ukraine conflict have affected global trade in grains, fertilizers and energy, requiring efficient management strategies to mitigate risks and ensure the profitability of livestock production. In this context, this study analyzed the economic viability of animals from the Pure Origin Zebu Program. The research was based on the hypothesis that cost management, especially nutrition and feed efficiency, directly influences the profitability of livestock production. The aim was to evaluate costs and technical-economic indicators in different production phases of purebred zebu cattle (PO). A total of 106 uncastrated male cattle of the Brahman, Guzerá, Sindi and Tabapuã breeds were used. They were evaluated in three production phases: pasture rearing in the dry season, pasture rearing in the wet season and feedlot fattening. The data was organized into economic statements, taking into account costs, cash flow and graphical trend analyses, and a correlation analysis was carried out. The results confirmed the economic viability of the system, with a profit of R$83.83 per arroba and a margin of 25%. Nutritional costs represented 64.71% of total production costs, standing out as the main factor impacting profitability. Feed conversion proved to be more relevant to profit than final carcass weight, highlighting the importance of feed efficiency. It can be concluded that strategic cost management, combined with genetic selection for feed efficiency, is fundamental to optimizing profitability and ensuring the competitiveness of Brazilian livestock in the face of the volatility of the agricultural market.